Unemployment and political trust across 24 Western democracies: Evidence on a welfare state paradox. (August 2021) - Giustozzi, Carlotta; Gangl, Markus
Set against the backdrop of the Great Recession, the paper explores the interplay of unemployment experiences and political trust in the USA and 23 European countries between 2002 and 2017. Drawing on harmonized data from the European Social Survey and the General Social Survey, we confirm that citizens' personal experiences of unemployment depress trust in democratic institutions in all countries. Using multilevel linear probability models, we show that the relationship between unemployment and political trust varies between countries, and that, paradoxically, the negative effect of unemployment on political trust is consistently stronger in the more generous welfare states. This result holds while controlling for a range of other household and country-level predictors, and even in mediation models that incorporate measures of households' economic situation to explain the negative effect of unemployment on trust. As expected, country differences in the generosity of welfare states are reflected in the degree to which financial difficulties are mediating the relationship between unemployment and political trust. Overlaying economic deprivation, however, cultural mechanisms of stigmatization or status deprivation seem to create negative responses to unemployment experiences, and these render the effect of unemployment on political trust increasingly negative in objectively more generous welfare states.